(3fUjMI Gdedhcs - (3Ydj Hf eMeO MHjH, CHh GdMSf GdeGhQOj,J (B450 (3g` s ((3ESeGYjd Hf SdjeGf Hf ESeGYjd GdHjLhQi s)
(3ChdgG (B:s
(3HMeO Gddg faJJM hfbhd eeeG GMedfG Ydi JCdja gPG GdcJGH HYO eG YdefG ef MK Gddg Ld PcQg GdYbdG ef YHGOg Ydi WdH GdCLQ s
(3BNQgG (B:s
(3hgPg ehYXI LGeYI JHjf Yf cKjQ ef CUhd aSGO GdeeGdc hGdCOjGf hUdGMgeG QCjfG Cf fNJe HG cJGHfG hhage Gddg hEjGfG ddSOGO hgOGfG hGjGge SHd GdQTGO s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B189s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1958s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdSjGSI hGdGLJeGYs